Masa Pembaharuan dan Kebangkitan Pendidikan Islam - Ramlah S; Bahaking Rama (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Efforts to renew Islamic education range from Islamic boarding schools, madrasas to elite Islamic schools. All of these have different backgrounds and of course this renewal is carried out so that Islamic educational institutions are known as quality institutions and play an optimal role in accordance with the expectations of society, this renewal effort is also so that the role of Islamic educational institutions can change from initially only processing in the interests of the afterlife, to being able to touch the field of worldly knowledge and can already place various fields of science and technology in the appropriate place. This study is a literature review with a qualitative descriptive method. The results of the study show that the factors that led to the emergence of the Revival in the field of Islamic education include the socio-religious situation of Egyptian society at that time which was full of taqlid, heresy and superstition as well as static thinking. Like Al-Afghani, Abduh saw that one of the causes of the backwardness of Muslims which was very concerning was the loss of intellectual tradition which in essence was freedom of thought. Three patterns of thought on Islamic educational renewal, the three patterns are the pattern of Islamic educational renewal that is oriented towards modern educational patterns in the West, which is oriented towards the renewal of Islamic education based on pure Islamic sources, and the pattern of educational renewal efforts that are oriented towards nationalism.